In situ preparation of a nanocomposite comprising graphene and α-Fe2O3 nanospindles for the photo-degradation of antibiotics under visible light. (2nd September 2020) - Arora, Komal; Karthikeyan, Sekar; Shiekh, Bilal Ahmad; Kaur, Manvir; Singh, Harjinder; Bhadu, Gopala Ram; Kang, Tejwant Singh
Abstract : Preparation of α-Fe2 O3 nanospindle (NS) decorated graphene sheets for antibiotic degradation. Abstract : Few layer thick graphene sheets are exfoliated in an aqueous medium by using iron containing imidazolium based ionic liquid (IL; [C16 mim][FeCl4 ]) in high yield exhibiting excellent dispersion stability. Subsequently, IL that stabilizes the graphene sheets is exploited for the in situ preparation of α-Fe2 O3 nanospindle (NS) decorated graphene sheets, for the first time. The prepared α-Fe2 O3 @graphene nanocomposite (NC) shows enhanced photocatalytic activity for the degradation of an antibiotic, sulfamethoxazole, under visible light. The enhanced photocatalytic activity of the NCs as compared to bare α-Fe2 O3 NSs is probed using computational simulations, where graphene is observed to sensitize α-Fe2 O3 NSs in the photoexcitation process. This increases the electron charge density in the conduction band of α-Fe2 O3 NSs, resulting in enhanced photocatalytic efficiency.